HOW CEO GLOBAL EXPOSURE AND GENDER DIVERSITY SHAPE MANAGERIAL ABILITY - INVESTMENT EFFICIENCY RELATIONSHIP IN STATE-OWNED ENTERPRISES - Anies Lastiati; Azahra Nur Alifah; Rini Dame Fransisca (Jurnal Bisnis dan Akuntansi, 2024)
This study aims to evaluate the impact of managerial ability (MA) on investment efficiency (IE) on state-owned companies (SOEs) in Indonesia. Using 169 data of SOEs in Indonesia from 2019-2021. This paper also assesses the impact of the CEOs’ global exposure and gender diversity board of directors on the MA-IE relationship. The result reveals that competent management links to higher knowledge and understanding on investment decision and its impact to the company in the long run. Hence, the more capable management is, the lower investment inefficiency will be. This study further finds that management who exposes to the global access and network through CEOs’ experiences in multinational companies will lessen the negative impact of managerial ability on company’s investment inefficiency. Further finding, however, could not prove that female presence in the SOEs board of directors has any impact on the managerial ability – investment efficiency relationship.